Peran Masyarakat Dalam Bidang Pendidikan Kesehatan Kesehatan Gigi Untuk Mendukung Transformasi Kesehatan - Salfiyadi, Teuku; Andriani; Elfi Zahara; Intan Liana (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Health education is important and the first step in increasing knowledge about health. The results of this service had a positive impact on cadres in increasing knowledge of dental health where the respondents' knowledge score before the intervention (pre-test) was in the sufficient category (62%), the largest distribution of respondents' knowledge immediately after the intervention (post test I) was in the good category (84%) and the largest distribution of respondents' knowledge one month after the intervention (post test II) was in the good category (100%). Shows that the largest distribution of respondents' practices before the intervention (pre-test) was in the sufficient category (64%). While the respondents' attitude scores after the intervention (post test I) were in the good category (92%), the largest distribution of respondents' practices one month after the intervention (post test II) was in the good category (96%). The conclusion is that the results of this service have succeeded in increasing cadres' knowledge of the importance of maintaining education from an early age. Apart from that, improving cadres' behavior will also increase the health of their families' teeth. With a regular and effective dental care routine, the risk of caries can be reduced.